literature review: hubungan picky eater dengan status gizi anak usia preschool - Achfa Kurnia Ridharini; Sih Ageng Lumadi; Evi Dwi Prastiwi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Picky eater behavior is picky eating behavior in children. Picky eaters will reject foods such as vegetables, fruit, and fish. Children will experience nutritional imbalances in food intake. This study aims to analyze whether there is a relationship between picky eater behavior and nutritional status in preschool age children. The method or design used is a literature review using the PICOS framework. Journal search using ScienceDirect, ProQuest, PubMed and Google Scholar databases. Journal criteria used in the last 5 years. The analysis in this study is synthesized in the form of a narrative. The results of this study indicate that 10 journals stated that there was a relationship between picky eaters and the nutritional status of preschool-aged children by being marked by children who did not want to try new foods and children only ate the foods they liked. Intake of food nutrition in children who behave picky eaters experience an imbalance, which is characterized by a lack of carbohydrates, fats, proteins, vitamins, minerals. In overcoming picky eater children, the role of parents or caregivers is very important by providing a variety of interesting food variations for children..